Quench dynamics in one-dimensional optomechanical arrays - Raeisi, Sadegh; Marquardt, Florian (Physical Review A, 2020)
Nonequilibrium dynamics induced by rapid changes of external parameters is relevant for a wide range of scenarios across many domains of physics. For waves in spatially periodic systems, quenches will alter the band structure and generate new excitations. In the case of topological band structures, defect modes at boundaries can be generated or destroyed when quenching through a topological phase transition. Here, we show that optomechanical arrays are a promising platform for studying such dynamics, as their band structure can be tuned temporally by a control laser. We study the creation of nonequilibrium optical and mechanical excitations in one-dimensional arrays, including a bosonic version of the Su-Schrieffer-Heeger model. These ideas can be transferred to other systems such as driven nonlinear cavity arrays.
CRIS-Team WoS Importer:2020-02-28